Characteristics of Quality Research - Efrita Norman; Enah Pahlawati; Abdul Husenudin (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Research is not a strange thing anymore for students who are taking the final semester, where one of the requirements for them to graduate is to complete a final project in the form of a research, as well as lecturers in the tridharma of higher education besides teaching is research, so this research has become a habit. However, many of the research results are not qualified, they only fulfill an obligation, so the purpose of this research is how to make quality research so that it is useful for many people. The method used in this study is a qualitative method using a literature study approach where the authors collect data, study, and analyze the literature published by books, journals, and magazine articles so as to obtain accurate and in-depth data about the characteristics of quality research. The results of this research are the characteristics of quality research, first of all, the problem must be clear and it really becomes a problem and needs an immediate solution or solution and Focus so that in collecting data it is true that the data can later be used in solving the problems that we examine, with The formulation of the problem and research objectives are correct and clear, so that the researcher will be more focused, efficient and effective. Second, the research objectives are related to things that are expected to be achieved through conducting research or presenting the results to be achieved after the research is completed. by kar Therefore, the formulation of research objectives must be consistent with the formulation of the problem and must reflect the research process. Third, it must be careful, so that later the research is truly valid according to the data and facts in the field. Fourth, the report is complete and systematic. In making the report, it must be complete with supporting data, namely: both primary data and secondary data, supporting theories must be clearly stated, and reports must be systematically arranged from the beginning to the end of the fifth must be precise in analyzing the data and the tools used must be in accordance with the data we will analyze the six conclusions and Suggestions must come from sources, namely the data we find in the field, not from personal opinions. The seven researchers must have integrity, namely a combination of all points one to six so as to produce quality research. Keyword :